Benchmarking in Federal Systems - Fenna, Alan (Forum of Federations, 2010)
Recent years have seen a rapidly growing interest in the use of benchmarking arrangements to improve policy performance in federal systems. This is a new development and one that is in its very early stages, but there is no doubting its significance. At issue here is the intersection of two things: a particular form of government and a particular form of management. Each is a complex matter in itself. How compatible is benchmarking with principles of federalism; and to what extent benchmarking can ‘add value’ to existing federal arrangements either by offering a superior mode of intergovernmental relations and/or by generating better substantive results for citizens? This paper looks at various benchmarking experiences in OECD-type federations and the European Union and draws tentative conclusions as to how complementary federalism and benchmarking might be.